Pengaruh Operating Cash Flow, Sales Growth, dan Inventory Turnover terhadap Return Saham, dengan Kepemilikan Manajerial sebagai Variabel Moderasi - Lainufar Nawalinnajah; Niswah Baroroh (Universitas Muhammadiyah Palembang, 2026)
This study aims to analyze the effect of operating cash flow, sales growth, and inventory turnover on stock returns, with managerial ownership as a moderating variable in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2021-2024. This study uses a quantitative approach with secondary data obtained from the companies' annual reports. Data analysis uses descriptive analysis, classical assumption tests, and Moderated Regression Analysis (MRA). The results show that operating cash flow and inventory turnover have a positive effect on stock returns, while sales growth has no effect on stock returns. Managerial ownership is unable to moderate the effect of operating cash flow, sales growth, and inventory turnover on stock returns. The novelty in this study is the inclusion of managerial ownership as a moderating variable.